Epicutaneous immunotherapy for peanut allergy treatment in pediatrics: A literature review - Fadya, Vannisa; Safira, Siti Sarah; Nabila, Amira Qisthy; Yufika, Amanda (Pediatric Sciences Journal, 2025)
Peanut allergy in children is a growing public health concern that significantly affects patients' quality of life. Although oral immunotherapy (OIT) has shown effectiveness in desensitizing allergic reactions, it is associated with a threefold increased risk of anaphylaxis compared to strict avoidance. As an alternative, epicutaneous immunotherapy (EPIT) has emerged as a promising therapy due to its favorable safety profile, ease of administration, and non-invasive nature. However, despite increasing interest in EPIT, there is still limited evidence assessing its efficacy and safety in pediatric populations. This literature review aims to summarize current findings on the mechanism of desensitization, clinical efficacy, safety, and impact on quality of life associated with EPIT in managing peanut allergy in children. Relevant articles were identified through database searches in PubMed, Cochrane, Science Direct, Scopus, and Google Scholar using Medical Subject Headings (MeSH) and keyword combinations such as "Epicutaneous Immunotherapy", "Peanut Allergy", and "Pediatric Allergy". EPIT works by delivering peanut allergens through a patch applied to intact skin. The allergen is taken up by Langerhans cells and presented to the immune system, triggering regulatory T-cell (Treg) responses that reduce allergic sensitivity. Viaskin© is the most clinically advanced EPIT delivery system currently available. Findings from clinical studies indicate that EPIT is effective in inducing desensitization, with a lower risk of systemic reactions compared to OIT. Furthermore, EPIT contributes to improved quality of life in children with peanut allergy. These results support EPIT as a promising therapeutic option for pediatric peanut allergy management.